Social cognitive approach in responding to mass media contents / Mohammad Yaacob - Yaacob, Muhammad (Faculty of Communication and Media Studies (FCMS), 2008)
Mass media play a very important role in the development of a society. Through symbolic communications, the media influence individual thoughts, affects and actions. much good has been achieved in the country through the efforts of media, but at the same, the society is also being served with undesirable messages. The relationship between messages (values, knowledge and appeals) portrayed by the media and the development of any society are also influenced by environmental variables and individual internal dispositions. The failure to learn positive messages has effected the Malay younger generations in negative ways, where more youngsters are seem practicing negative values they learned from mass media. This paper is constructed to described how environmental factors and personal dispositions of Malay people in Malaysia could influence their response to media. This paper also proposes ways for young people to do self examination when reacting to media information so that they can learn the positive and leave the negative.